El impacto del origen del capital en la implementación de prácticas de responsabilidad social empresarial, el caso de Uruguay (Has the origin of capitals a relevant impact on implementing corporate social responsibility? The Uruguayan case) - Ana Bogiloff; Natalia Melgar (Oñati Socio-Legal Series)
We assess whether being socially responsible is influenced by the origin of capitals and we examine the different views of the firms regarding CSR, in the case of a small open economy, Uruguay. Our dataset comes from the 2007 Corporate Social Responsibility Survey. The contributions of this research are threefold. Firstly, while a great part of the research on this issue is based on special cases, we employ and draw conclusions from a representative survey. Secondly, we deal with an unexplored issue: the incidence of the origin of capitals in motivating social responsible behavior. Finally, we highlighted the need of strengthening the communication channels between the firms and the public.